The Combination of Curaxin CBL0137 and Histone Deacetylase Inhibitor Panobinostat Delays KMT2A-Rearranged Leukemia Progression - Xiao, Lin; Karsa, Mawar; Ronca, Emma; Bongers, Angelika; Kosciolek, Angelika; El-Ayoubi, Ali; Revalde, Jezrael L.; Seneviratne, Janith A.; Cheung, Belamy B.; Cheung, Laurence C.; Kotecha, Rishi S.; Newbold, Andrea; et al. (Frontiers in Oncology, 2022)
Rearrangements of the Mixed Lineage Leukemia (MLL/KMT2A) gene are present in approximately 10% of acute leukemias and characteristically define disease with poor outcome. Driven by the unmet need to develop better therapies for KMT2A-rearranged leukemia, we previously discovered that the novel anti-cancer agent, curaxin CBL0137, induces decondensation of chromatin in cancer cells, delays leukemia progression and potentiates standard of care chemotherapies in preclinical KMT2A-rearranged leukemia models. Based on the promising potential of histone deacetylase (HDAC) inhibitors as targeted anti-cancer agents for KMT2A-rearranged leukemia and the fact that HDAC inhibitors also decondense chromatin via an alternate mechanism, we investigated whether CBL0137 could potentiate the efficacy of the HDAC inhibitor panobinostat in KMT2A-rearranged leukemia models. The combination of CBL0137 and panobinostat rapidly killed KMT2A-rearranged leukemia cells by apoptosis and significantly delayed leukemia progression and extended survival in an aggressive model of MLL-AF9 (KMT2A:MLLT3) driven murine acute myeloid leukemia. The drug combination also exerted a strong anti-leukemia response in a rapidly progressing xenograft model derived from an infant with KMT2A-rearranged acute lymphoblastic leukemia, significantly extending survival compared to either monotherapy. The therapeutic enhancement between CBL0137 and panobinostat in KMT2A-r leukemia cells does not appear to be mediated through cooperative effects of the drugs on KMT2A rearrangement-associated histone modifications. Our data has identified the CBL0137/panobinostat combination as a potential novel targeted therapeutic approach to improve outcome for KMT2A-rearranged leukemia.